2022
DOI: 10.1002/joc.7883
|View full text |Cite
|
Sign up to set email alerts
|

Snow depth variability across the Qinghai Plateau and its influencing factors during 1980–2018

Abstract: As a crucial component of the climate system, snow cover plays an important role on surface energy budgets, hydrological cycles and socioeconomic development. This paper investigated the spatiotemporal patterns of snow depth across the Qinghai Plateau (QP) during 1980–2018 based on passive microwave (PMW) satellite observation and reanalysis products. The study identified the relationships between the changes in PMW snow depth and topographic features and revealed the impact of climatic variables (air temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…For instance, in the Greater Khingan Mountains, an increase of SWE/SD and, for the Hengduan, Kunlun, and the Chinese part of the Himalayan Mountains, a decrease in SWE/SD was observed. However, for other regions such as the Changbai, Lesser Khingan, and Tianshan Mountains, the studies partly show conflicting results, which, however, can be attributed to varying input data, the experimental design, as well as the study domain [80,100,196,197,211,241]. For most other regions in the Northern Hemisphere, the studies are not in agreement or the observed changes are not significant.…”
Section: Results Of Long-term Studiesmentioning
confidence: 93%
See 2 more Smart Citations
“…For instance, in the Greater Khingan Mountains, an increase of SWE/SD and, for the Hengduan, Kunlun, and the Chinese part of the Himalayan Mountains, a decrease in SWE/SD was observed. However, for other regions such as the Changbai, Lesser Khingan, and Tianshan Mountains, the studies partly show conflicting results, which, however, can be attributed to varying input data, the experimental design, as well as the study domain [80,100,196,197,211,241]. For most other regions in the Northern Hemisphere, the studies are not in agreement or the observed changes are not significant.…”
Section: Results Of Long-term Studiesmentioning
confidence: 93%
“…For instance, the decline in SWE/SD is stronger in North America than in Eurasia [13,121,124,125,132]. In addition, many studies observe a stronger decrease in spring than in winter [13,100,124,240]. In addition, remote sensing-based products show a greater decrease than other products (models or in situ) [100,125,132,241].…”
Section: Results Of Long-term Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…There are typical interannual variations in the SP on the TP. Ground-measured measurements and remote sensing data have been extensively used in recent decades to better understand these changes (Ma et al, 2022;Notarnicola, 2020). Remote sensing is beneficial in high-elevation areas where few ground-measured measurements are obtainable (Huang et al, 2022a).…”
Section: Introductionmentioning
confidence: 99%
“…However, SP is also closely associated with other meteorological factors, such as wind and humidity. But their quantitative influence on SP on the TP has not been discussed further (Ma et al, 2022;Xie et al, 2017). Topographic characteristics (Guo et al, 2022) and vegetation greenness (Qi et al, 2021) are also considered responsible for SP.…”
Section: Introductionmentioning
confidence: 99%